2021
DOI: 10.1111/jwas.12836
|View full text |Cite
|
Sign up to set email alerts
|

Novel findings in sea cucumber's digestive capacities: Enzymatic activities in the respiratory tree, implications for aquaculture

Abstract: There is a demand for proper feed and feeding strategies in the growing sea cucumber aquaculture. The digestive system of holothurians seems to increase nutrient assimilation through the respiratory tree (RT), but digestive functioning in this organ has not been investigated. This study evaluated the enzymatic activity of the cytosolic leucine alanine peptidase (leu-ala) and acid phosphatase, the membranelinked aminopeptidase-N (APN), the bile salt-activated lipase, laminarinase (LAM), and β-glycosidase (BGL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 98 publications
(114 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, the estimated dietary phosphorus requirement from these quadratic regression analyses appears lower than the published reports on fish (0.72-1.57%, [28,[51][52][53]), shrimp (1-2%, [26,[54][55][56][57]), crab (1.59-1.68%, [24]), and abalone (1-1.2%, [25]), implicating that sea cucumber may have an specific phosphorus acquisition mechanism. This is proved by a recent physiological findings indicated the phosphatase exhibited comparable activity levels in the respiratory tree segments of sea cucumber Isostichopus badionotus [58]. Another evidence from an early P 32 isotope study also revealed that sea cucumber absorbed a limited amount of phosphorus from the environment through the integumentary surface and respiratory tree [59].…”
Section: Intestinal Oxidation Resistancementioning
confidence: 73%
“…On the other hand, the estimated dietary phosphorus requirement from these quadratic regression analyses appears lower than the published reports on fish (0.72-1.57%, [28,[51][52][53]), shrimp (1-2%, [26,[54][55][56][57]), crab (1.59-1.68%, [24]), and abalone (1-1.2%, [25]), implicating that sea cucumber may have an specific phosphorus acquisition mechanism. This is proved by a recent physiological findings indicated the phosphatase exhibited comparable activity levels in the respiratory tree segments of sea cucumber Isostichopus badionotus [58]. Another evidence from an early P 32 isotope study also revealed that sea cucumber absorbed a limited amount of phosphorus from the environment through the integumentary surface and respiratory tree [59].…”
Section: Intestinal Oxidation Resistancementioning
confidence: 73%